Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Find the first three terms of the sequence defined below, where [tex] n [/tex] represents the position of a term in the sequence. Start with [tex] n = 1 [/tex].

[tex]\[ f(n) = -2n + 7 \][/tex]

[tex]\[
\begin{aligned}
&\text{Term 1: } f(1) = \square \\
&\text{Term 2: } f(2) = \square \\
&\text{Term 3: } f(3) = \square
\end{aligned}
\][/tex]


Sagot :

To find the first three terms of the sequence defined by [tex]\( f(n) = -2n + 7 \)[/tex], we'll follow these steps for [tex]\( n = 1, 2, \)[/tex] and [tex]\( 3 \)[/tex]:

1. Determine the first term ([tex]\( f(1) \)[/tex]):
- Substitute [tex]\( n = 1 \)[/tex] into the function:
[tex]\[ f(1) = -2(1) + 7 \][/tex]
- Perform the multiplication:
[tex]\[ f(1) = -2 \cdot 1 + 7 = -2 + 7 \][/tex]
- Add the results:
[tex]\[ f(1) = 5 \][/tex]


2. Determine the second term ([tex]\( f(2) \)[/tex]):
- Substitute [tex]\( n = 2 \)[/tex] into the function:
[tex]\[ f(2) = -2(2) + 7 \][/tex]
- Perform the multiplication:
[tex]\[ f(2) = -2 \cdot 2 + 7 = -4 + 7 \][/tex]
- Add the results:
[tex]\[ f(2) = 3 \][/tex]


3. Determine the third term ([tex]\( f(3) \)[/tex]):
- Substitute [tex]\( n = 3 \)[/tex] into the function:
[tex]\[ f(3) = -2(3) + 7 \][/tex]
- Perform the multiplication:
[tex]\[ f(3) = -2 \cdot 3 + 7 = -6 + 7 \][/tex]
- Add the results:
[tex]\[ f(3) = 1 \][/tex]

Thus, the first three terms of the sequence are:
[tex]\[ 5, 3, 1 \][/tex]